If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(t + -6) + 5t = 5(3t + 3) + -12 Reorder the terms: 10(-6 + t) + 5t = 5(3t + 3) + -12 (-6 * 10 + t * 10) + 5t = 5(3t + 3) + -12 (-60 + 10t) + 5t = 5(3t + 3) + -12 Combine like terms: 10t + 5t = 15t -60 + 15t = 5(3t + 3) + -12 Reorder the terms: -60 + 15t = 5(3 + 3t) + -12 -60 + 15t = (3 * 5 + 3t * 5) + -12 -60 + 15t = (15 + 15t) + -12 Reorder the terms: -60 + 15t = 15 + -12 + 15t Combine like terms: 15 + -12 = 3 -60 + 15t = 3 + 15t Add '-15t' to each side of the equation. -60 + 15t + -15t = 3 + 15t + -15t Combine like terms: 15t + -15t = 0 -60 + 0 = 3 + 15t + -15t -60 = 3 + 15t + -15t Combine like terms: 15t + -15t = 0 -60 = 3 + 0 -60 = 3 Solving -60 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| w(3w+5)=492 | | (3+7y)+(-4+y)= | | (3x+2)(3x^2+2x+1)= | | 3x+8=-15x+17 | | 6q+q+4q=55 | | 5x+8=-15x+17 | | -54.06x-5=-951.6x+254.6 | | x+2.2=8.8 | | 1.2x+3.8=0.8x+1.6 | | 5x^2+21x=20 | | 13a-8a=45 | | w=3(w-12)+30 | | -36=-1+5x | | 3x-1/21-5=3 | | 12y+3y=30 | | 2(x+1)-6=0 | | 3y+7=19 | | 2c^2=16 | | -8x+10=-6x+6 | | 17+4x-5=4(x+3) | | (3x^2-5x+4)+(x^2-4x-7)= | | 3(3x-2)-29=3x+1 | | 5a^2+13a=6 | | m^2+5m+7=0 | | 44-99x^2=0 | | 6x-(5x+8)=-4 | | 9n-3n+5= | | 6x-5x+8=-4 | | 5x+3=4(x-4) | | w^2=13w-40 | | 3r^2=-r | | 3n^2=32-4n |